Speckled ZnO Nanograss Electrochemical Sensor for Staphylococcus epidermidis Detection. Issue 6 (1st January 2017) - Purwidyantri, Agnes; Chen, Ching-Hsiang; Chen, Liang-Yih; Chen, Chien-Chung; Luo, Ji-Dung; Chiou, Chiuan-Chian; Tian, Ya-Chung; Lin, Chan-Yu; Yang, Chia-Ming; Lai, Hsin-Chih; Lai, Chao-Sung
Abstract : Zinc oxide nanograss (ZnONG) decorated with gold (Au) nanospeckles is demonstrated as a sensing platform for bacterial DNA hybridization in this study. Thermal evaporation of 5 nm Au on hydrothermally synthesized ZnONG generates highly dense speckles, which contributes to an approximately two-fold enhancement of the effective surface area and diffusion coefficient in cyclic voltammetry (CV) measurement compared to the non-speckled nanograss. Selective capture of molecular probes from our predesigned sequence of S. epidermidis 16S rRNA onto nanospeckled ZnONG indicated a specific interaction with the DNA target from this prevalently isolated skin pathogen through hybridization screening. The fabricated DNA biosensor demonstrated great ability to quantify a wide range of complementary DNA target, from 10 pM to 1 μM. Moreover, it attained an impressive limit of detection (LOD) of 0.506 pM, as determined by the charge-transfer resistance (RCT ), upon DNA hybridization in an electrochemical impedance spectroscopy (EIS) analysis. The proposed structure of the hybrid Au-speckled ZnONG effectively improved the electro-catalytic properties and electron migration of electrochemical DNA detection due to the increment of the surface area, which consequently renders this structure a potential platform for array-based DNA sensor development.